2021
DOI: 10.20944/preprints202106.0618.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Validation of a Brief Screening Instrument for Chemical Intolerance in a large U.S. National Sample

Abstract: Keywords: Chemical Intolerance, Drug Intolerance, Food Intolerance, QEESI, BREESI, Multiple Chemical Sensitivity, Toxicant-induced Loss of Tolerance, Prevalence

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Based on these results, we suggest that caution be taken when interpreting results from different cultures. This current study is consistent with two previous US studies showing the BREESI to be an efficient and reliable CI screening tool [27,28]. We are hoping that the BREESI will lead healthcare providers across the globe to consider how CI may underlie a wide range of chronic and acute health problems.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Based on these results, we suggest that caution be taken when interpreting results from different cultures. This current study is consistent with two previous US studies showing the BREESI to be an efficient and reliable CI screening tool [27,28]. We are hoping that the BREESI will lead healthcare providers across the globe to consider how CI may underlie a wide range of chronic and acute health problems.…”
Section: Discussionsupporting
confidence: 90%
“…In two prior studies, the BREESI demonstrated excellent positive and negative predictive values (97% and 95%, respectively) and good specificity and sensitivity (90% and 87%, respectively) in a clinical sample of 297 primary care patients [27]. Using a US population-based sample of over 10,000 Americans, the BREESI also demonstrated good positive and negative predictive values (83% and 97%, respectively) and good specificity and sensitivity (93% and 91%, respectively) [28].…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations